The Impact of Corporate Social Responsibility on Sustainable Development Performance - Mediating Effect of Dual Green Innovation - Sun, Qiong; Wang, Zhongsheng; Zhu, Yaxin; Liao, Bin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
Green sustainable development remains the cornerstone of China’s economic progress and the guiding principle for the transformation and advancement of its manufacturing sector. Aligned with China’s objectives of achieving a "carbon peak" by 2030 and "carbon neutrality" by 2060, expediting the green development of manufacturing enterprises and enhancing their sustainable development performance are crucial to ensuring their long-term health and prosperity amid transformation and upgrading. This holds the key to realizing sustained and healthy growth for manufacturing enterprises as they navigate the process of transformation and advancement. According to stakeholder theory and natural resource-based theory, this study evaluates Chinese listed manufacturing enterprises, utilizing panel data spanning 2012-2021 to empirically analyze the relationship between CSR, dual green innovation, sustainable development performance, and redundant resources in these enterprises. A model is constructed to explain the effect of CSR on sustainable development performance. The findings demonstrate that CSR significantly cultivates both continuous and disruptive green innovation, elevating corporate sustainability performance. Continuous and disruptive green innovation represents positive mediating factors in this relationship. The moderating effect analysis indicates that non-sedimentary redundant resources exert a positive moderating effect between CSR and dual green innovation, while the moderating effect of sedimentary redundant resources between the two remains insignificant. Further exploration indicates that in the short term, continuous green innovation exhibits a more significant and positive effect on sustainability performance. Conversely, in the long run, disruptive green innovation demonstrates a greater positive effect on sustainability performance. Considering these conclusions and the specific characteristics and requirements of manufacturing enterprises, this paper proposes relevant recommendations to assist enterprises in effectively enhancing their sustainable development performance.